Regional and Seasonal Variations in Honey Pollen Composition: Advances in Melissopalynology and Techniques for Honey Quality Assessment - AlkaRani; Sunita Verma (The Bioscan, 2025)
Melissopalynology, the study of pollen in honey, plays a critical role in understanding the relationship between floral diversity and honey quality. This paper explores the regional and seasonal variations in honey pollen composition and the techniques used to analyze these variations. We present a comprehensive overview of significant studies in melissopalynology, focusing on the impact of floral diversity on honey characteristics across different regions, including India, Oman, and Andhra Pradesh. Advances in pollen preparation, analysis methods, and the use of statistical and multivariate approaches are discussed. Techniques for honey fraud detection, such as melissopalynology, are highlighted to ensure honey authenticity. The study emphasizes contributions from leading figures in the field and the role of pollen analysis in quality control. By integrating regional findings and methodological advancements, this paper provides a holistic view of honey’s pollen composition, its seasonal variability, and emerging techniques for improving honey quality assessment.